Challenges of electric vehicle adoption in Indonesia: Revealing the hidden factors affecting purchase intention - Astuti, Rifelly Dewi; Susanto, Agung Arry (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – Recently, electric vehicles (EVs) have seen significant development worldwide. Indonesia has responded by implementing various policies to support the adoption of EVs, which are touted as the future environmentally friendly transportation solution. However, in Indonesia, the purchase intention for EVs still needs to reach expectations, reaching only 14,93% of the target in 2023. This study analyzes the antecedents of benefit factors determining the intention to buy an electric vehicle. This study will fill the gap in earlier research by comprehensively examining the factors that influence EV purchase intention in Indonesia.Design/methodology/approach – This study will fill the gap in earlier research by comprehensively analyzing the factors that influence EV purchase intention in Indonesia. This study will empirically examine the relationship between perceived usefulness, perceived ease of use, perceived risk, EV knowledge, public involvement, and purchase intention, as well as the antecedents of perceived usefulness, perceived ease of use, and perceived risk. This study uses a quantitative method with a survey design to gain an in-depth understanding of the factors influencing the purchase intention of electric vehicles in Indonesia. The survey involved 957 potential electric vehicle users in Indonesia who have never bought an EV but have sufficient interest and knowledge about EVs. The research instrument was a validity and reliability-tested questionnaire used to collect accurate and consistent data.Findings – This study found that although respondents had strong perceptions of the benefits of electric vehicles (perceived usefulness), this did not automatically lead to high purchase intentions. Another surprising finding was that perceived risk also did not directly affect purchase intention. This suggests the presence of other factors inhibiting purchase intention, which need to be identified and addressed.Research limitations/implications – This research contributes significantly to the literature on adopting electric vehicles (EVs). Perceived ease of use has a positive effect on purchase intention. The results of this study indicate that perceived ease of use does not significantly affect the purchase intention of electric vehicles.Practical implications – The findings of this study provide several practical implications for electric vehicle manufacturers, marketers, and policy makers.Originality/value – This research offers a comprehensive approach to understanding the factors that influence electric vehicle (EV) purchasing interest in Indonesia, by including previously overlooked variables such as risk perception, public involvement, and knowledge about EVs. Additionally, this research focuses on the Indonesian context, providing valuable insights into the unique challenges and opportunities in EV adoption in the country, which can form the basis for strategies and policies to promote sustainable transportation.